2019
DOI: 10.1097/aog.0000000000003114
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Severe Maternal Morbidity at Delivery Hospitalization

Abstract: has been reviewed by the Editorial Board and by special expert referees. Although it is judged not acceptable for publication in Obstetrics & Gynecology in its present form, we would be willing to give further consideration to a revised version. If you wish to consider revising your manuscript, you will first need to study carefully the enclosed reports submitted by the referees and editors. Each point raised requires a response, by either revising your manuscript or making a clear and convincing argument as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…The excess weight gain was more common in overweight and obese women (61% and 53%, respectively), which is consistent with the literature [29,30]. Previous studies underscored increases in SMM only among women with excess weight gain [14,16]; however, our results show an increase in maternal death/SMM also in women with low gestational weight gain. Prior studies were smaller and were often restricted to women with term pregnancy [14,16].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The excess weight gain was more common in overweight and obese women (61% and 53%, respectively), which is consistent with the literature [29,30]. Previous studies underscored increases in SMM only among women with excess weight gain [14,16]; however, our results show an increase in maternal death/SMM also in women with low gestational weight gain. Prior studies were smaller and were often restricted to women with term pregnancy [14,16].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies underscored increases in SMM only among women with excess weight gain [14,16]; however, our results show an increase in maternal death/SMM also in women with low gestational weight gain. Prior studies were smaller and were often restricted to women with term pregnancy [14,16]. Our sensitivity analyses show that such restriction provides different results for perinatal outcomes, as women with low and excess weight gain are more likely to deliver preterm.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Nevertheless, a recent meta-analysis showed that self-reported weight of women of reproductive age differs only slightly from direct measures [35]. Finally, beyond BMI, gestational weight gain, a recently highlighted risk factor for adverse pregnancy outcomes [36], was not taken into account in our analysis, because related data were not available. Nonetheless, a noteworthy study from the state of Washington did not show any substantial modification in the associations between BMI and maternal outcomes after controlling for gestational weight gain [11].…”
Section: Limitationsmentioning
confidence: 99%